2020
DOI: 10.1145/3392882
|View full text |Cite
|
Sign up to set email alerts
|

DreamCatcher: Exploring How Parents and School-Age Children can Track and Review Sleep Information Together

Abstract: Parents and their school-age children can impact one another's sleep. Most sleep-tracking tools, however, are designed for adults and make it difficult for parents and children to track together. To examine how to design a family-centered sleep tracking tool, we designed DreamCatcher. DreamCatcher is an in-home, interactive, shared display that aggregates data from wrist-worn sleep sensors and self-reported mood. We deployed DreamCatcher as a probe to examine the design space of tracking sleep as a family. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…For instance, sometimes parents' treatment goals involve increasing the variety in their child's diet, not necessarily for nutritional purposes, but for the sake of social acceptance at school. CSCW research on behavioral health has begun to direct more attention toward goals of patient autonomy and self-management [15,16,25,29,33,38,39], and we suggest more of this type of work with an explicit focus on the social model of disability and on promoting the autonomy of disabled children. For example, instead of Jim having to spend eight weeks in intensive treatment, what if Jim's friends learnt to accept his gastrostomy tube and perhaps assisted him in administering food through this tube?…”
Section: Disability and Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sometimes parents' treatment goals involve increasing the variety in their child's diet, not necessarily for nutritional purposes, but for the sake of social acceptance at school. CSCW research on behavioral health has begun to direct more attention toward goals of patient autonomy and self-management [15,16,25,29,33,38,39], and we suggest more of this type of work with an explicit focus on the social model of disability and on promoting the autonomy of disabled children. For example, instead of Jim having to spend eight weeks in intensive treatment, what if Jim's friends learnt to accept his gastrostomy tube and perhaps assisted him in administering food through this tube?…”
Section: Disability and Autonomymentioning
confidence: 99%
“…Hong and colleagues have shown how technology can enable pediatric patients and their families to explore and interpret complex clinical data such as radiology reports [15], and support the evolving partnership between patient and clinician as adolescents grow to become more involved in their care [16]. Similarly, Pina et al's work within the home has shown how family-based design can help children learn about self-monitoring their daily behaviors [38] and self-managing their health conditions [39].…”
Section: Behavioral Interventions In Hcimentioning
confidence: 99%
“…The practitioner community developed ample applications of data visualization in mobile apps & websites (refer to [56,57] for curated practices). Data visualization is also commonly used for mobile form factors, such as smartphones and tablets, in research prototypes (e.g., [16,22,41,42,55,60]) developed by UbiComp and Human-Computer Interaction researchers. However, research specifcally focusing on mobile data visualization is sparse and much of the mobile visualization research has been carried out with tablets [10].…”
Section: Visual Exploration Of Personal Datamentioning
confidence: 99%
“…An exciting avenue for future research is to explore different ways to share tracking responsibilities between parents and children, as well as ways to balance data access and the amount of information shared. While one option is to employ parents as "guides" in teaching children how to self-track, another option is to have parents track same or different data alongside their children (e.g., [59]).…”
Section: Collaborative Tracking and Reflectionmentioning
confidence: 99%